ANALISIS RISIKO PENYEBAB STUNTING PADA BALITA DI PUSKESMAS RAMBATAN II KABUPATEN TANAH DATAR - Tika Ramadanti; Cici Apriza Yanti (Jurnal Endurance, 2023)
ABSTRACT The prevalence of cases in Indonesia is 37.2%. Stunting means one of indicators of cronic nutrion status that describe barrier of growing because malnutrion in long period. Community health centre of Rambatan experiences of stunting. The objective of this research is to know factors of causes stunting on baby in community health centre rambatan II tanah datar regency in 2018. Type of this research is analytic survey with case control design. The sample of this research is stunting baby and not stunting baby.Analyzing data is done by using univariate and bivariate with chi-square test with 95% degree reliance. The result of the research shows that 54 respondents (58.7%) high knowledge, 50 respondents (54.3%) have infection story, 55 respondents (59.8%) have bad on diet, 59 respondents (64.1%) exclusive breast, 46 respondents (50.0%) have stunting baby. There is correlation between meaningful knowledge with stunting occurrence (p=0.005). there is correlation between infection history with stunting occurrence (p=0.005). there is correlation between diet with stunting occurrence (p=0.005). and there is correation between exclusive breast and stunting occurrence (p=0.005). Based on the resul of the research, it can be concluded that stunting occurrence causes bad on diet. It is expected to health workers in order to give training about the importance on diet to avoid stunting. Keywords: knowledge, infection diseases history, diet, breast feeding, stunting ABSTRAK Prevalensi kasus stunting di Indonesia 37,2%. Stunting merupakan indikator status gizi kronis yang menggambarkan terhambatnya pertumbuhan karena malnutrisi yang jangka panjang. Puskesmas Rambatan II tersebut banyak yang mengalami Stunting. Tujuan peneliti ini adalah untuk mengetahui ” Faktor-Faktor Penyebab Stunting Pada Balita di Puskesmas Rambatan II Kabupaten Tanah Datar Tahun 2018. Jenis penelitian survey analitik dengan desain case control. Objek penelitian adalah balita yang mengalami stunting 46 responden dan balita yang tidak mengalami stunting 46 responden. Pengolahan data dilakukan dengan analisis univariat dan bivariat dengan uji Chi-Square dengan derajat kepercayaan 95 %. Hasil penelitian 54 responden (58,7%) pengetahuan tinggi. 50 responden (54,3%) memiliki riwayat infeksi, 55 responden (59,8%) memiliki pola makan kurang baik. 59 responden (64,1%) ASI Ekslusif. 46 responden (50,0%) memiliki balita stunting. Ada hubungan bermakna antara pengetahuan dengan kejadian stunting (p= 0,005). Terdapat hubungan antara riwayat penyakit infeksi dengan kejadian stunting (p= 0,005), Terdapat hubungan antara pola makan dengan kejadian stunting (p= 0,005). Terdapat hubungan ASI Ekslusif dengan kejadian stunting (p= 0,005). Disimpulkan bahwa ada hubungan pengetahuan,riwayat penyakit infeksi, pola makan dan ASI Ekslusif dengan Stunting. Diharapkan kepada tenaga kesehatan agar dapat memberi penyuluhan tentang pentingnya pola makan untuk mencegah stunting. Kata Kunci: Pengetahuan, Riwayat Penyakit Infeksi, Pola Makan, ASI Ekslusif, Stunting